Multiple response optimization of the effect of thyme essential oil against Listeria monocytogenes in ground meat at different times and temperatures - Tornuk, Fatih; Yilmaz, Mustafa Tahsin; Ozturk, Ismet; Sagdic, Osman; Arici, Muhammet; Durak, Muhammed Zeki; Bayram, Mustafa (POLISH SOC VETERINARY SCIENCES EDITORIAL OFFICE, 2016)
Response surface methodology was used to optimize conditions (e.g., Thyme oil concentration [0.0-0.57%] and storage temperature [0.0-14.14 degrees C]) for inhibiting the growth of L. monocytogenes (log cfu/g) in ground meat. Additionally, the effect of the variables; namely, temperature and concentration on mu(max) (maximum specific growth rate, In cfu/g/h) values was also evaluated using a proposed combined model. The best fitting second order polynomial models were developed for each response using multiple linear regression analysis with backward elimination regression (BER) procedure. In this paper, multi-response surfaces using, desirability function approaches were successfully applied to determine optimum operating conditions. Under these optimum treatment and storage parameters, L. monocytogenes populations at hours 6, 24, 48, 72 and 96 were 6.12, 5.96, 5.88, 5.81 and 5.41 log cfu/g and 0.0011n cfu/g/h, respectively and mu(max) value 0.0011n cfu/g/h. At the end, the proposed combined model is described numerically and experimentally.
Keywords: Baranyi model; central composite design; Listeria monocytogenes; ground meat; thyme essential oil; SALMONELLA-TYPHIMURIUM; LACTIC-ACID; GROWTH; MODEL; ORIGANUM; KINETICS; BEEF; Veterinary Sciences